The War of 1812: The Rise of American Nationalism - Hanseling, Paul (My University, 2016)
On June 18, 1812, United States President, James Madison, signed a Declaration of War against Great Britain. What brought these two nations to such a dramatic impasse? Madison's War Message to Congress gives some hint as to the American grievances: impressment of American sailors; unnecessary, "mock" blockades and disruption of American shipping; violations of American neutral rights; and incursions into American coastal waters.[1] By far, the most vocal point of contention was impressment, or the forcible enlistment of men in the navy. For their part, Great Britain viewed every measure disputed by Americans as a necessity as they waged war against the Continental advances of Napoleon and for maintaining the economic stability of the British people. However, the war erupted despite repeal of the contentious British Orders-in-Council on June 23, 1812. And while Madison cited impressment and maritime rights as the primary causes, what other factors influenced this march to war? How do national honor, Canada, Native Americans, the western frontier, and internal politics also play a significant role? [1] James Madison, "War Message to Congress," in The War of 1812: Writings from America's Second War of Independence, ed. Donald R. Hickey (New York: The Library of America, 2013), 1-9.
Bachelor of Arts (BA)
Keywords: 1812; United States; Great Britain; Nationalism; War Hawks; Impressment